The Relationship Between HbA1c Levels and Severity of COVID-19 Patients with Diabetes Mellitus at Haji General Hospital, East Java Province - Ambar, Nabil Salim; Rahmadina, Muhimmatul Aaliyah; Subkhan, Mohammad; Ariana, Audy Meutia (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
One of the factors influencing SARS-CoV-2 infection is comorbidity. Diabetes mellitus is a comorbidity with a high mortality rate. Poor glucose control in patients can affect cellular immune responses and increase morbidity and mortality associated with infections. The severity of COVID-19 is classified into 5 levels: asymptomatic, mild, moderate, severe, and critical. HbA1c is a good test for identifying the diabetes status of COVID-19 patients. According to the American Diabetes Association, HbA1c levels are considered controlled if <7% and uncontrolled if ≥7%. This study aims to analyze HbA1c levels in COVID-19 patients with diabetes mellitus from 2020 to 2022. This study uses the productive age category (15-64 years). To determine the relationship between HbA1c levels and the severity of COVID-19 patients with diabetes mellitus at Haji General Hospital, East Java Province, from 2020 to 2022. This research employs a cross-sectional, analytical observational method with a consecutive sampling technique involving 96 hospitalized COVID-19 patients. Data collection was conducted through medical record observation. The majority of the samples were male, with an average age of 53 years. The Fisher Exact Test yielded a p-value of 0.13, which is greater than the significance level (0.05), indicating no significant relationship between HbA1c levels and the severity of COVID-19 in diabetic patients. There is no significant relationship between HbA1c levels and the severity of COVID-19 in diabetic patients at Haji General Hospital, East Java Province.